2021
DOI: 10.1111/acem.14237
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐access physiotherapy to help manage patients with musculoskeletal disorders in an emergency department: Results of a randomized controlled trial

Abstract: Objectives The objective was to evaluate the effects of direct‐access physiotherapy on patients presenting with a musculoskeletal disorder (MSKD) to the emergency department (ED) on clinical outcomes and use of health care resources. Methods We conducted a randomized controlled trial in an academic ED in Québec City, Canada. We included patients aged 18 to 80 years with minor MSKD. The intervention group had direct access to a physiotherapist (PT) in the ED immediately after triage and prior to physician asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Cross-sectional data were acquired during the baseline assessment performed as part of a single center randomized controlled trial conducted between September 2018 and March 2019 in an Academic ED in Quebec City (Canada). 50 In this trial, management by a physiotherapist in the ED compared to usual care resulted in a decrease in the level of pain and pain interference on function for up to 3 months post-initial consultation, as well as a reduction in the number of recommended imaging studies, the amount of prescription and non-prescription medication used, and repeat visits to the ED for the same condition. 50 The study was approved by the Research Ethics Committee of the CHU de Québec – Université Laval and registered at the US National Institutes of Health #NCT04009369.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Cross-sectional data were acquired during the baseline assessment performed as part of a single center randomized controlled trial conducted between September 2018 and March 2019 in an Academic ED in Quebec City (Canada). 50 In this trial, management by a physiotherapist in the ED compared to usual care resulted in a decrease in the level of pain and pain interference on function for up to 3 months post-initial consultation, as well as a reduction in the number of recommended imaging studies, the amount of prescription and non-prescription medication used, and repeat visits to the ED for the same condition. 50 The study was approved by the Research Ethics Committee of the CHU de Québec – Université Laval and registered at the US National Institutes of Health #NCT04009369.…”
Section: Methodsmentioning
confidence: 92%
“… 50 In this trial, management by a physiotherapist in the ED compared to usual care resulted in a decrease in the level of pain and pain interference on function for up to 3 months post-initial consultation, as well as a reduction in the number of recommended imaging studies, the amount of prescription and non-prescription medication used, and repeat visits to the ED for the same condition. 50 The study was approved by the Research Ethics Committee of the CHU de Québec – Université Laval and registered at the US National Institutes of Health #NCT04009369. Patients presenting to the ED were recruited if they had a potential peripheral or vertebral minor MSKD (eg, sprain, strain, tendinitis, low back pain, neck pain) and if given a triage score of 3 (urgent), 4 (less urgent) or 5 (non urgent) based on the Canadian Emergency Department Triage and Acuity Scale classification.…”
Section: Methodsmentioning
confidence: 92%
“…Emerging evidence from recent studies emphasizes the potential role of DAPT in reducing costs associated with the care pathway: fewer visits, fewer exams, and a more active approach that may allow patients with MSD to achieve an earlier and better functional recovery [ 4 , 12 ]. Moreover, two recent randomized controlled trials have reported DAPT as an effective strategy even for patients with acute musculoskeletal pain in the emergency department [ 13 ] and a quick and safe adjunct to usual general practitioner-led primary care [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These promising results of DAPT increased the interest in the topic leading to several novel publications [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Ohja et al were the first to provide preliminary evidence that DAPT was associated with better outcomes and fewer costs than a referred pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported that primary contact physiotherapist management can reduce the use of services and resources during the ED stay. [8,[26][27][28][29]55] This research project will fill an important need in the literature by providing an in-depth analysis of the costs and efficiency of the considered models of care . Indeed, this project will help identify the most efficient ED model of care.…”
Section: Discussionmentioning
confidence: 99%